Identificación de alternativas para la reducción de costos en el proceso de transporte de caña manual en un ingenio del Valle del Cauca (2023)
project that arises from the need of a sugar mill to reduce its operating costs and ultimately achieve higher profits. This is part of a range of projects defined by the company's management in conjunction with the management area (improvement area) and with the help of the owners of the different processes. In the transportation process for the manual cane harvest at the sugar mil l, it was aimed to apply tools from the DMAIC methodology, defining its objectives according to each stage to ultimately achieve the savings. Firstly, the goal of average weight per wagon was sought to be defined. The options proposed by the methodology were reviewed with the support of management to set an achievable but challenging goal.